The Distance to Reference Communities Index (DRCI): a new tool to assess communities' restoration success - Hugo, Fontès; Christian, Marquis; Franck, Torre; Grillas, Patrick; Dutoit, Thierry; Mesléard, François (Restoration ecology, 2024)
The concept of a reference ecosystem is fundamental in restoration ecology, especially in assessing the success of ecological restoration projects. In response to criticism, it has undergone conceptual evolutions in its definition and use in the last decades. Even though there is still a need to develop statistical methods and analyses to account for reference variability. Here, we focus on two original and one literature‐based calculation methods for designed indexes, which all aim to compare a community to be assessed (undergoing restoration) with a variable set of reference communities. These methods either use the average reference situation (species composition and abundance) as the restoration target or on the contrary, allow any reference site to be considered a relevant target. We compare the results of these methods by analyzing a simulated dataset. We then illustrate the application of the most relevant index by a real case study that compared a created Mediterranean temporary pond to a panel of 27 reference ponds located in the south of France. The results show that the Distance to Reference Communities Index (DRCI) correctly measures differences in species composition and abundance between an assessed and a reference panel of communities. It takes into account the variability of the reference communities, while the use of other indexes focuses on unrealistic average and fixed reference values. DRCI is complementary to a detailed ecological interpretation and to the use of other commonly used indexes, by giving a synthetic metric.